Biology and ecological functional of Genus Crassostrea (Bivalvia: Ostreidae): a review - Lili Kasmini; Agung Setia Batubara (Depik, 2022)
The genus Crassostrea has an important role for community life in coastal and mangrove ecosystems. In this article, we try to review in detail the ecology, biology, and ecological functions of Crassostrea spp. Furthermore, we also review about 25 species of Crasostrea that exist in the world and also have a high level of adaptation. Based on ecological functional, Crassostrea acts as an efficient engineer of ecosystems, where in forming ecosystems, in nutrient cycling, in reducing anthropogenic eutrophication, shelter area, breeding grounds, and as a link between benthic-pelagic. In addition, high Crassostrea communities can form reefs and serve as ecologically important for diverse species.Keywords:Marine BivalvesCommunity Anthropogenic EcosystemsFunctional